Effect of measurement method on an earmuff’s frequency response - Młyński, Rafał; Żera, Jan (Archives of Acoustics, 2007)
Light, medium and heavy earmuffs’ amplitude frequency response was measured usingtransmission loss technique with a microphone placed in subject’s ear (MIRE – microphonein real ear) and on an artificial test fixture (ATF). Measurements were conducted in frequencyrange up to 9 kHz employing maximum length sequence (MLS). This method shows detailsof earmuffs’ amplitude frequency response, in contrast to sound attenuation data obtainedin octave bands according to the EN-ISO 4869-1 standard. The study compared ATF datawith results measured on a person when soft tissues influenced the ripples of the obtainedfrequency response. Results were also judged against the sound attenuation data of the realear at threshold (REAT) method used in certification of hearing protectors.